EFEKTIFITAS BIMBINGAN KELOMPOK TEKNIK EMPTY CHAIR DAN SELF TALK UNTUK MENINGKATKAN KETERAMPILAN KOMUNIKASI INTERPERSONAL SISWA - Fauzi Aldina (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2018)
This study aims to examine the impact of guidance group of empty chair technique and self talk technique to improve interpersonal communication skill of students in SMK Mataram Semarang. Research method used experiment, randomized pretest-posttest control group design design involving research subjects as many as 20 people selected by proposive from 82 students. The results showed the technique of empty and effective self talk technique to improve interpersonal communication skills of students with different level of kefeektifan guidance group of self talk technique is higher than the technique of empty chair. The guidance of empty chair technique group and selftalk technique is effective to improve interpersonal communication skill of SMK Mataram Semarang students.